Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1186/s12884-020-2748-y
|View full text |Cite
|
Sign up to set email alerts
|

Trends in smoking during pregnancy by socioeconomic characteristics in the United States, 2010–2017

Abstract: Background: Maternal smoking during pregnancy remains a public health concern in the United States (US). We examined whether the prevalence of smoking during pregnancy decreased between 2010 and 2017 and how trends differed by demographic subgroups. Methods: We used 2010-2017 data from the National Center for Health Statistics. Rao-Scott Chi-Square tests were performed to compare characteristics between smoking and nonsmoking groups. Cochran-Armitage tests and logistic regression were used to assess overall ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(63 citation statements)
references
References 15 publications
3
55
1
4
Order By: Relevance
“…This finding was supported by M.Mohsin (2011) and Erin Passmore (2015) in their respective studies reporting women from low Socio-economic status continued smoking during pregnancy (45) (46) . S.Agazba (2020) reported that maternal smoking prevalence is high in less educated women (47) . J.…”
Section: Discussionmentioning
confidence: 99%
“…This finding was supported by M.Mohsin (2011) and Erin Passmore (2015) in their respective studies reporting women from low Socio-economic status continued smoking during pregnancy (45) (46) . S.Agazba (2020) reported that maternal smoking prevalence is high in less educated women (47) . J.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking during pregnancy in the United States has been slowly trending downwards for the past several decades (Meernik and Goldstein 2015;Azagba et al 2020). Nevertheless, a substantial number of American women still smoke for some portion of their pregnancy (Azagba et al 2020), risking premature delivery, low birth weight, and congenital defects (Scherman et al…”
Section: Cigarette Taxes Experienced As a Teenager And Smoking Among Mothersmentioning
confidence: 99%
“…On the one hand, the causes of smoking may not have their roots in the same fundamental causes as disparities in other health outcomes. Indeed, on average, Black women are less likely to smoke when pregnant than White women ( Azagba, Manzione, et al, 2020 ; Li et al, 2018 ). Smoking patterns are also highly amenable to social policy, such as higher cigarette taxes and other anti-smoking laws ( Azagba, Shan, & Latham, 2020 ; Evans & Ringel, 1999 ; Friedson & Rees, 2020 ; Levy & Meara, 2006 ; Lien & Evans, 2005 ), suggesting that the root causes of smoking patterns may be variable rather than fundamental.…”
Section: Introductionmentioning
confidence: 99%